Efficacy of antiviral therapy in patients with post-hepatitis C liver cirrhosis: is hyperuricaemia a potential adverse effect?. Issue 1 (12th December 2020) - Elsayed, Amr; M Abdelraheem, Ehab; Hassan, Hatem; Abbas, Abbas; Hassnine, Alshymaa
Abstract : Hepatitis C virus (HCV) related liver cirrhosis is considered a major health problem; sofosbuvir (SOF)/ledipasvir (LDV) and SOF/daclatsvir (DACLA) are very promising direct antiviral agents (DAAS) especially in treating HCV genotype 4 which is the main genotype in Egypt. Uric acid elevation was reported in many systemic diseases and might be elevated during direct antiviral therapy. The aim is to evaluate efficacy and safety of SOF/LDV and SOF/DACLA plus ribavirin in treating HCV related child A liver cirrhosis and assess hyperuricaemia as a potential adverse effect to this regimen. Methods: This prospective observatinal study included 128 HCV naive child A cirrhotic patients divided into two groups (77 patients were treated with SOF 400 mg, DACLA 60 mg and ribavirin 600 mg and 51 patients were treated with SOF 400 mg, LDV 90 mg and ribavirin 600 mg) for 12 weeks, during the treatment complete blood count, creatinine, bilirubin, alanine transaminase, aspartate transaminase and serum uric acid were monitored, HCV RNA quantitative PCR at 12 weeks after the end of treatment was done. Results: Response to treatment in SOF/LDV (sof/led) group is about (98%), response to treatment in SOF/DACLA (sof/dacla) group is about (96%). Hyperuricaemia was noticed in 17.6% of patients received sof/led and in 15.5% of those received sof/dacla. Conclusion: SOF+LDV and SOF+DACLA plus ribavirin regimens are highly effective in treating chronic HCV patients with compensated liver cirrhosis. Hyperuricaemia is considered a potential adverse effect to DAAS containing ribavirin and may lead to serious side effects such as renal impairment.